Family climate and its relationship to children's mental health (Journal of the College of Basic Education, 2023)
Psychoanalysts emphasized the importance of the first family experiences in the behavior of children.and their attitudes, which have an important impact on their psychological and social development, and the formation of their personalities.functionally and dynamically. A happy family prepares a healthy psychological environment for normal growth and leads to happiness.Children and their mental health, while the troubled family is a bad psychological environment for growth.serve as a breeding ground for behavioral deviations and psychological and social disorders(Zahran (1978: 17). The nature of what the child experiences in relation to the relationships within his family is what determinesTo a large extent, whether he will develop properly psychologically or not (Rasheed: 1995a).As the basis of mental health, as psychologists see it, is based on the connectionpsychological according to what the child tells him of an intimate and permanent relationship with his family members, as the child finds inSuch a relationship is the satisfaction of his psychological needs, and this relationship is full of experiences thatIt is at the beginning of his life and then it takes many forms that have a great impact on his relations with his family members.And in his future relationships with others. (Stagier, 1974, P:90).In fact, the family climate, which includes warmth and stability, may be a factor.Support for the individual while he is facing the pressures of life, and on the contrary, the turbulent family climatemay turn into an instigator indirectly to push the individual to breach standards and notCommitment to it (Hassan (2001: 263), and when the family fails to provide the family climate thatIt helps to teach its members how to achieve a balance between communication needs with others.and their independent needs, the door is open to various forms of wrong communication.Which ends up disturbing the atmosphere of the family and turning it into a focal point that generates turmoil and even injuring some of them.I sing it in the clear, clear and straightforward way (Kafi 1999: 159).From here, the research problem is represented in the following questions: Do students enjoy a climateGood family and good mental health, and is there a relationship between family climate and mental health?children? What is the nature of this relationship?